The Impact of Rural Women’s Access to Economic Resources on the Wellbeing of Their Households in Asuret Sub-county, Soroti District - Sharon Evelyne Abeja (Uganda Christian University, 2024)
The research investigated the impact of rural women’s access to economic resources on the well-being of their households in Asuret Sub County, Soroti district. The study identified a gap in rural women access to economic resources despite government efforts in programs like UWEP, EMYOOGA, PDM, and NAADS. The study adopted purposive sampling technique, qualitative research design, data analysis through coding and data collection methods of interviews and focused group discussions. The study found access to friendly micro-credit, responsive public policy management, protection of women, and access to land and property rights key determinants for access to economic resources, rural women access to economic resources as not the only factor responsible for the well-being of their households. Future researchers should consider assessing the factors for economic prosperity among women. The study concluded that there was a strong positive relationship between women access to economic resources and the well-being of their households.